Microclimate and Wind Regime of Three Typical Landscapes in the Northeastern Ulan Buh Desert - Luo, Fengmin; Xiao, Huijie; Gao, Junliang; Ma, Yuan; Li, Xing; Li, Junran; Miri, Abbas; Cao, Qiqi; Xin, Zhiming (Frontiers in Environmental Science, 2022)
Knowledge of the microclimate and wind regime of different land landscapes can be used to support natural resources development and agricultural productivity in desert areas. The aim of this study is to provide a theoretical basis and technical support for the management of Ulan Buh Desert Oasis and the comprehensive prevention and control of sandstorms from the surrounding desert in northern China. We examined the microclimate and wind regime of three landscapes—desert, desert–oasis ecotone and oasis, and discussed the factors underlying the observed variations. Similar patterns were found in annual temperature, annual relative humidity, and wind speed between the desert, desert–oasis, and the oasis. Compared with the desert and the desert–oasis ecotone, average annual temperature and wind speed in the oasis were lower by 2.56%–5.38% and 32.99%–37.05%, respectively. Average annual relative humidity in the oasis was higher than other areas by 1.31–2.57%. The desert, desert–oasis ecotone, and the oasis were dominated by westerly winds. Wind direction was relatively stable in the oasis and variable in the desert and desert–oasis ecotone. There was intermediate wind energy fields in the desert and the desert–oasis ecotone, and a low wind energy field in the oasis. In the desert–oasis ecotone, drift potential (DP), resultant drift potential (RDP) and resultant drift direction (RDD) were 231.87 VU, 97.21 VU, and 104.33°, respectively. In the desert, DP was 228.45 VU, RDP was 92.65 VU and RDD was 76.05°. In the oasis, the DP was 61.85 VU, RDP was 38.04 VU, and RDD was 92.97°. In the desert and the desert–oasis ecotone, sediment transport potential was the highest in spring, second highest in autumn, third highest in winter, and the lowest in summer. In the oasis, it was the highest in winter, second highest in autumn, third highest in spring, and the lowest summer. There are complex variations in the dominant sediment transport directions in the desert and desert–oasis ecotone in the study area. Variations in the dominant sediment transport direction in the oasis are less complicated and are associated with the seasons. The oasis is primarily threatened by sandstorms from the south-southeast in spring.